Integrating structural education and architectural projects : a contemporary approach at the University of Brasília, Brazil - Menezes, Érika Stella Silva (2024)
This paper discusses the potential realignment of structural design concepts in architecture’s teaching and learning process, aiming enhancement and adaptation to a new reality within the construction field. It is recognized that the curricular parameters of a course should focus on developing the ability to acquire, synthesize, and apply knowledge, promoting a resilient education that equips professionals to resolve emerging conflicts and generate new solutions tailored to the reality of each context. In the field of Architecture and Urbanism, it is crucial to suggest the realignment of existing Structures courses, as Architecture and Structure are inseparable, and understanding the behavior of structures under new social demands is part of the architects' legal responsibilities. Such understanding is imperative for professionals to perform their duties with assertiveness and safety, ensuring stability of the conceived form. However, there are indications of potential issues in the teaching of Structures in architecture and urbanism schools, such as purely expository lectures and curricula distant from current professional practice. The methodology applied in this article is bibliographic research, which consists of a systematic analysis of the literature related to the theme of teaching and learning structures in undergraduate architecture programs.